Investigating Leadership Styles at the National Level and Their Impact on Education Policy: An Opportunist Authoritarian Perspective - Virra Krisnafitriana; Imam Gunawan (Faculty of Education Universitas Negeri Malang, 2025)
The purpose of the current study is to investigate leadership styles at the national level and their impact on education policy from the perspective of opportunistic authoritarian leadership in two Southeast Asian countries (Indonesia and Singapore). To achieve the study objective, content analysis was used. The results confirmed that although opportunistic authoritarian leadership can have a negative impact on the organization, however, this leadership style maintains security, order and team performance. Moreover, this leadership style provides advantages in terms of efficiency and consistency due to its nature of creating a climate of certainty, tight control, and quick execution. Under opportunistic authoritarian leadership, the leaders of both countries maintained various educational policies and impacted on economic growth and sustainable human resource development. The theoretical and practical implications of the findings are discussed. Limitations and future research opportunities are suggested.